Manajemen Ekstrakulikuler Pramuka Dalam Upaya Peningkatan Nilai Karakter Siswa SMA - zaki, zakiyah; Winata, Ganjar; Badrun, Badrun (Universitas Muhammadiyah Surakarta, 2024)
This study aims to describe the implementation of Scout extracurricular activities and the character values contained in Scout extracurricular activities at SMAN 1 Talang Padang. This study intends to find an overview of management strategies especially in scout extracurricular activities. This type of research is descriptive qualitative in examining field phenomena that occur. This research was conducted on principals, vice principals for curriculum, scout coaches, and student activities both in the field and indoors. Data collection is carried out by means of interviews, observation, and documentation. The results are the application of good management to extracurricular scouts to shape the character is carried out in 4 stages, namely: planning the learning environment, organizing the learning environment, directing the management, and controlling the management of the learning environment. The planning stage includes the recruitment of scout coaches by the principal, time management, financial management, preparation of work programs, and preparation of materials. Organizing is done by giving responsibility to the homeroom teacher to direct students to participate in extracurricular scouts, and giving responsibility to the scout coach. The implementation of activities is carried out once a week. Briefings are made by the principal to the scout leader so that the activity can run well. Controlling is a supervision carried out to find out whether scout activities are running well or not